A Case of Metastatic Extramammary Paget's Disease Responding to Trastuzumab plus Paclitaxel Combination Therapy - Fumie Hanawa; Takashi Inozume; Kazutoshi Harada; Tatsuyosi Kawamura; Naotaka Shibagaki; Shinji Shimada (Karger Publishers, 2011)
There is no effective treatment for advanced extramammary Paget's disease (EMPD). The human epidermal growth factor receptor 2 (HER2) protein is often overexpressed in EMPD. Trastuzumab is a humanized monoclonal antibody against HER2 used in the treatment of breast cancers in which HER2 is overexpressed. We report a case of advanced EMPD in which trastuzumab and paclitaxel combination therapy was effective. The patient was a70-year-old Japanese woman who presented with EMPD on the vulva and multiple metastatic lymph nodes. Immunohistochemical staining revealed strong HER2 protein expression in the primary tumor and metastatic lymph nodes. The patient received trastuzumab and paclitaxel. After 4 courses of this regimen, the mass on the vulva and the metastatic lymph nodes regressed. Our findings may imply that trastuzumab plus paclitaxel combination therapy is useful for the treatment of advanced EMPD overexpressing HER2.